Pendekatan Fuzzy Logic Dalam Penentuan Mahasiswa Berprestasi Pada Fakultas Ilmu Komputer Universitas Sjakhyakirti - Malahayati; Ade Sukma Wati; Gina Agiyani (JSAI (Journal Scientific and Applied Informatics), 2023)
Academic achievement is one of the qualities in education for the factors and elements that play a role in the educational process. The quality of education can be seen from the side of student learning outcomes (academic field), namely the value of the Grade Point Average (GPA). Student participation in competitions (non-academic fields) is also one of the elements of the quality of education implementation, so that students are considered capable of functionally utilizing their knowledge. Determining outstanding students can help Sjakhyakirti University in monitoring and evaluating the education sector carried out by the Quality Assurance Unit (UPM). To determine student achievement, the Tsukamoto method of fuzzy logic approach is used. This method was chosen because the Tsukamoto method's fuzzy logic is a method for drawing conclusions from Tsukamoto's vague conclusions. In a fuzzy logic system, there are several operational stages including: 1. Fuzzification. 2. reasoning engine or interference engine. 3. basic rules (fuzzy rules). 4. defuzzification. With the Tsukamoto method of fuzzy logic calculations with the python tool, the results are determined accurately and quickly.